The impact of antihypertensive pharmacotherapy on interplay between protein-bound uremic toxin (indoxyl sulfate) and markers of inflammation in patients with chronic kidney disease - Kaminski, Tomasz W. (Int Urol Nephrol, 2019)
PURPOSE: Indoxyl sulfate (IS) is one of the most potent uremic toxins involved in chronic kidney disease (CKD) progression, induction of inflammation, oxidative stress, and cardiovascular diseases occurrence. It is proved that hypertension is a common CVD complication and a major death risk factor as well as contributes for decline in a renal function. The aim of our study was to investigate how implementing of antihypertensive therapy impact IS concentrations and the associations between IS and markers of renal function, inflammation and oxidative stress. METHODS: Study was conducted on 50 patients diagnosed with CKD and hypertension, divided into three groups: without hypotensive therapy (CKD-NONE), hypotensive monotherapy (CKD-MONO), and hypotensive polypharmacotherapy (CKD-POLI), and 18 healthy volunteers. The markers of inflammation [interleukin-6, tumor necrosis factor-alpha (TNF-α), high-sensitive C-reactive protein (hs-CRP), neopterin, ferritin], oxidative status [superoxide dismutase (Cu/Zn-SOD), antibodies against oxidized low-density lipoprotein (oxLDL-abs)], and selectins were determinate using immunoenzymatic methods. IS levels were assayed using high-performance liquid chromatography and other parameters were analysed using routine laboratory techniques. Then cross-sectional analysis was performed. RESULTS: Elevated levels of IS, indicators of kidney function, markers of inflammation and blood pressure values were observed in each CKD subgroups. There was no effect of antihypertensive therapy on IS levels between studied groups, as well as there was no clear relationship between IS and blood pressure values in each studied group. The positive associations between IS and Cu/Zn SOD, neopterin, hs-CRP, creatinine and neutrophils/lymphocytes ratio were observed in CKD-NONE and CKD-POLI subgroups. Additionally, in CKD-POLI group IS positively correlated with TNF-α, ferritin and neutrophils. In CKD-MONO group, IS was positively related to oxLDL-abs, neopterin, E-selectin and creatinine, whereas it was inversely associated with hs-CRP. CONCLUSIONS: Our study showed for the first time that the antihypertensive therapy has no impact on IS levels in CKD patients with hypertension. However, the introduction of the antihypertensive therapy modified the dependencies between IS and the studied markers of kidney function, inflammation, oxidative stress and hematological parameters that are crucial for mortality and morbidity amongst the CKD patients with hypertension. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11255-018-02064-3) contains supplementary material, which is available to authorized users.